The Effect of Job Characteristics and Ethical Climate on Job Satisfaction with Organizational Commitment as a Mediating Variable - Erlina Ari Jayanti; Muryati; Survival (Journal of Management Research and Studies, 2024)
This study aims to obtain empirical evidence of the influence of job characteristics and ethical climate on job satisfaction with organizational commitment as a mediating variable. The population in this study were all employees at the Probolinggo Regional Inspectorate, totaling 122 employees. The determination of the number of samples using the Slovin formula, which is 94 people. The data analysis technique used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4.0. The results of the study indicate that better job characteristics can encourage increased job satisfaction. Better job characteristics can encourage increased organizational commitment. Better ethical climate can encourage increased job satisfaction. Better ethical climate can encourage increased organizational commitment. Higher organizational commitment can encourage increased job satisfaction. Organizational commitment plays a role in mediating part of the influence of job characteristics on job satisfaction. Organizational commitment plays a role in mediating part of the influence of ethical climate on job satisfaction.